TINDAK PIDANA DAN PENANGGULANGANNYA - Sudarilah, Sudarilah (MAJALAH ILMIAH WIDYA, 2012)
Multi dimensional crisis in 1988 was one of the factors which made the community were very vulnerable and fragile as well asnumerous legal irregularities and criminal acts that result invarious losses which could threaten the continuity in the life of nation andstate. The purpose of this paper is to discuss the problem of crime and increase public awareness and responsibility to participate increating a safe, calm and peaceful. The method is based on library data and observations in the community. The conclusion that itneed to be addressed by involving all citizens of both repressive and preventive, so as to promote the smooth development and thecreation of national well-being of society.